Tracking the COVID-19 vaccines: The global landscape - Tushar Yadav; Swatantra Kumar; Gourav Mishra; Shailendra K. Saxena (Human Vaccines & Immunotherapeutics, 2023)
COVID-19, a respiratory infectious disease, occurs due to Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). Millions of individuals around the world have been impacted by the illness, which has gravely threatened human health. The development and active involvement of varied vaccines against the COVID-19 have played a great and relieving role in controlling the life-threatening disease. Both the conventional and advanced vaccine platforms are available now to develop vaccines against COVID-19. Therefore, the present systematic review focuses on the global landscape of the COVID-19 vaccines and their current status. Among COVID-19 vaccines, virus like particles (VLPs), subunit vaccines, DNA, RNA-based vaccines, viral vector-based vaccines, inactivated and live-attenuated vaccines are the major contenders and are currently in various phase of clinical trials. Protein subunit, RNA-based and non-replicating viral vector-based platforms have been used majorly. Nevertheless, inactivated virus vaccine has been utilized clinically around the world. The clinical trials revealed that most of the vaccines have local or systemic effects after vaccination and varied efficacy against SARS-CoV-2 and its variants. However, further studies are necessary to refine the technology to minimize adverse effects and improve the safety and efficacy. Abbreviations COVID-19: Coronavirus disease 2019; SARS-CoV-2: Severe acute respiratory syndrome coronavirus-2; VLPs: Virus like particles; WHO: World Health Organization; E: Envelope; M: Membrane; S: Spike; N: Nucleocapsid; PRISMA: Preferred Reporting Items for Systematic Reviews and Meta-Analyses; FDA: Food and Drug Administration; LNP: lipid-nanoparticle; AZD1222: ChAdOx1 nCoV-19; BNT162b2: Pfizer-BioNTech mRNA vaccine; mRNA-1273: Moderna vaccine; Ad26.COV2.S: Johnson and Johnson – Janssen’s vaccine; Gam-COVID-Vac: Sputnik Vaccine; NVX-CoV2373: Novavax vaccine with Matrix-M™ adjuvant.